A Review of Postgraduate Theses on Integrating the Environmental Dimension of Sustainable Development into Curricula (Universitas Pendidikan Indonesia, 2026)
The aim of this study is to examine the master's and doctoral theses published between 2015 and 2024 on the inclusion of the environmental dimension of sustainable development in curricula. Document analysis method was used in the study, and 104 theses prepared between 2015 and 2024 on the environmental dimension of sustainability were included in the sample. In the descriptive analysis of the data, the findings were presented as percentages and frequencies. The findings revealed that mostly master's theses were prepared on the environmental dimension of sustainability; these studies were conducted in the field of Science courses, the keyword